2022
DOI: 10.1007/s00296-022-05246-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced echo intensity in vastus medialis is associated with worsening of functional disabilities and symptoms in patients with knee osteoarthritis: a 3 years longitudinal study

Abstract: Patients with knee osteoarthritis (OA) experience muscle quality loss, and is characterized by the enhanced echo intensity (EI) of the vastus medialis (VM) muscles and a high extracellular water-to-intracellular water (ECW/ICW) ratio of the thigh. This study aimed to elucidate the association between muscle degeneration and the worsening of functional disabilities and symptoms in patients with KOA over 3 years duration. Thirty-three patients with KOA who completed follow-up over 3 years were included in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…This discrepancy could be due to differences in the severity of knee OA; previous studies [7,13] included patients with advanced knee OA, but the current study targeted participants with early knee OA. The association of VM intraMAT with KSS function scores was consistent with a previous study in advanced knee OA [14]. Given that the minimum clinically significant difference in KSS function scores after total knee arthroplasty was 4.1 points [29], our findings that quadriceps 1% higher intraMAT was associated with a 3.88-point reduction in KSS functional score appear to be clinically significant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This discrepancy could be due to differences in the severity of knee OA; previous studies [7,13] included patients with advanced knee OA, but the current study targeted participants with early knee OA. The association of VM intraMAT with KSS function scores was consistent with a previous study in advanced knee OA [14]. Given that the minimum clinically significant difference in KSS function scores after total knee arthroplasty was 4.1 points [29], our findings that quadriceps 1% higher intraMAT was associated with a 3.88-point reduction in KSS functional score appear to be clinically significant.…”
Section: Discussionsupporting
confidence: 91%
“…As the presence of early OA was not significant in the regression model using VM intraMAT, a higher VM intraMAT seemed to play a mediating role in the relationship between early knee OA and functional disabilities. Our results also showed that a higher VM intraMAT was associated with the worsening of KSS Although it is known that an increase in intraMAT of the VM is associated with knee pain in advanced knee OA [14], the current study is the first to confirm similar associations in the pre-stage of knee OA development. As this study had a cross-sectional design, the causal relationship between knee symptoms and VM intraMAT infiltration in early knee OA could not be determined.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Others show the negative effects of ipsilateral and contralateral muscle asymmetry, both structural and functional, and the potential importance of the ability of muscle to contract in a coordinated and timely fashion. Others show cases identified as having poor vastus medialis muscle quality or the presence of excess knee extensor intramuscular fat deposits tend to show a higher degree of osteoarthritis disease severity at an early disease stage [80,87]. Others show knee muscle coordination rather than knee muscle strength may be the more salient pathogenic factor [88].…”
Section: Discussionmentioning
confidence: 99%
“…Other data, for example that by Rutherford, et al, imply a key role for muscle fatigue rather than muscle strength in this regard, but a role for altered muscle activation mechanisms and inflammation may likewise play a key role in this regard [78,79]. Yet again, alternate evidence implies muscle 'thickness' may be the salient variable that influences knee joint osteoarthritis according to Tanagushi, et al, and Yoon, et al, [80,81].…”
Section: Additional Findingsmentioning
confidence: 97%